Development of Floating Rice Cultivation Technology in Community-Based Peat Swamp Land - Aris Slamet Widodo; Gatot Supangkat; Mulyono Mulyono; Bahrul Ulum (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Peat swamp farming has great potential to increase food security from local potential. One of the technological innovations of cultivation on peat swamp land is by applying floating rice cultivation. This study aims to assess the success rate of implementing floating rice cultivation technology on peat swamp land in East Kalimantan. The method used is participatory action research with the community in one of the villages in East Kalimantan, namely Minta Village, Penyinggahan District, West Kutai Regency. Floating rice was applied using a 1.5 x 6 m bamboo raft with a total of 40 rafts. The rice varieties used were SR (Sri Republik) Super Genjah 75 HST rice. The results of the study showed that the plant height reached 90 cm, with 32 tillers, and 32 floating rice panicles. The average grain yield was 30 grams/clump or equivalent to 5 tons/ha assuming land use efficiency of 80%. The obstacles in floating rice cultivation in peat swamp land are the presence of pests in the form of sundep in the growth phase and sparrows in the rice grain production phase. In an effort to accelerate the adoption of floating cultivation technology, intensive socialization and education are needed. Keywords: Agricultural production, Cultivation technology, Floating rice, Innovation technology, Peat swamp land.